Euthanasia: Practices applied by the countries of the European Union - Κοζαμάνη (Alexandra Kozamani) Αλεξάνδρα (Bioethica, 2019)
Euthanasia is one of the issues that bioethics deals with, which is one of the outmost importance. Furthermore it is very up-to-date. In Greece and in most countries of the European Union euthanasia has not been subject to specialized legislation. It is only occasionally debated, resulting in tension and conflict. On one hand, people have the right to self determination, so the end of life should be among them. On the other hand, life is considered to be of the highest value and it is the duty of healthcare personnel to guard and preserve it by any means, using their expertise and knowledge. In this paper, a brief report is made to the practices used across countries in the European Union regarding the end of life. Most countries are opposed to euthanasia while acknowledging the right of a patient to refuse or receive treatment. Only three countries have passed bills that legalize euthanasia under strict conditions. The rest, due to sensitivity in this matter, have not yet proceeded in reforming their laws accordingly. It seems that society does not have the necessary reassurances so that they can engulf that issue guarding the true will of a person.